Bone-on-Bone Contact on Radiograph is not a Prerequisite for Successful Outcome in Fixed-Bearing Medial Unicompartmental Knee Arthroplasty—A 10-Year Follow-Up Study - Wong, Khai Cheong; Lee, Merrill; Liow, Lincoln; Lo, Ngai-Nung; Yeo, Seng-Jin; Chen, Jerry (The Journal of Knee Surgery, 2021)
Introduction Patients without bone-on-bone osteoarthritis are excluded from mobile-bearing unicompartmental knee arthroplasty due to higher revision rates and poorer outcomes. However, we do not know if the same indication applies to fixed-bearing unicompartmental knee arthroplasty implants. Our study aims to compare functional outcomes and revision rates in patients with and without bone-on-bone arthritis undergoing fixed-bearing medial unicompartmental knee arthroplasty.Materials and Methods We reviewed 153 fixed-bearing medial unicompartmental knee arthroplasties in a single institution. Patients were divided into four groups based on joint space remaining measured on preoperative radiographs. Group 1 included knees with bone-on-bone contact; group 2 included knees with less than 2 mm joint space; group 3 included knees with 2 to 4 mm joint space; group 4 included knees with more than 4 mm joint space. Patients were followed up for 10 years postoperatively and assessed using the Oxford Knee Score, the Functional Score and Knee Score from the Knee Society Clinical Rating Score, and the Short Form 36 Health Survey.Results There was no difference in terms of demographic data and preoperative scores. Postoperative Knee Society Functional Score was found to be lower in group 1 as compared with the other groups. There was no difference between the four groups of patients in terms of Knee Society Knee Score, Oxford Knee Score, and Physical Component Summary and Mental Component Summary Scores from the Short Form 36 Health Survey. There was no difference in terms of survivorship free from all-cause revision at a minimum of 10 years' follow-up.Conclusion Symptomatic patients with varying degrees of arthritis on preoperative radiographs had comparable clinical outcomes. We conclude that symptomatic patients with clinical and radiographic evidence of medial compartment osteoarthritis of any grade can benefit from a fixed-bearing medial unicompartmental knee arthroplasty.
Keywords: unicompartmental knee arthroplasty; fixed-bearing; bone-on-bone; radiograph